Advancing urban adaptation where it counts: reshaping unequal knowledg e and resource diffusion in networked Indonesian cities - Geldin, Samuel (Environment and Urbanization, 2019)
Climate adaptation literature vocalizes the need for transnational mun icipal networks (TMNs) to expand activities in vulnerable medium-sized cities, but little work has examined the granular extent of city part icipation and processes constraining TMN growth. This study explores t he effectiveness of TMNs in reaching adaptation outcomes and how finan cial, material, and knowledge exchanges of TMNs tend to exclude adapta tion in high-priority intermediary cities. Nearly 40 semi-structured i nterviews with Indonesian city actors and a preliminary catalogue of c ities participating in TMNs reveal that risk-averse selection criteria , insufficient impact assessments, and duplicative institutional effor ts reinforce disparities between primary and intermediary cities. To e ffectively build adaptive capacity in the most vulnerable regions, TMN s should remove participation barriers for intermediary cities, improv e incentives for institutional collaboration, and adopt more rigorous evaluative metrics. These results directly inform the governance, reso urce allocation, and operational goals of TMN stakeholders to advance distributive climate justice.